Clinical and Pathological Analysis of 10 Cases of Eosinophilic Pustular Folliculitis - Li Y; Chen G; Zhou X; Zheng X; Zhang M; Yao X; Lu J; Hu X (Dove Medical Press, 2023)
Yuan Li,1,2,* Gaihe Chen,3,* Xin Zhou,4,* Xiaole Zheng,1,* Ming Zhang,3 Xiaojuan Yao,1 Jiejie Lu,1 Xiaohuan Hu1 1Department of Cosmetic Dermatology, The Fifth People's Hospital of Hainan Province, Haikou, Hainan, People's Republic of China; 2Department of Dermatology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, People's Republic of China; 3Department of Dermatology, The Fifth People's Hospital of Hainan Province, Haikou, Hainan, People's Republic of China; 4Medical Administration Department, The Fifth People's Hospital of Hainan Province, Haikou, Hainan, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaohuan Hu; Jiejie Lu, Department of Cosmetic Dermatology, The Fifth People's Hospital of Hainan Province, No. 8 Longhua Road, Longhua District, Haikou, Hainan, 570100, People's Republic of China, Email 872114382@qq.com; lujiejie677@163.comAbstract: We conducted a retrospective analysis of clinical and pathologic data from January 2020 to June 2023, focusing on 10 patients diagnosed with eosinophilic pustular folliculitis at our dermatology clinic. Four of the ten patients had the first rash on the face, five on the trunk, and one on the palms and feet, all of which were initially scattered papules that gradually increased and fused into erythematous plaques with a circular distribution. Seven had pustules with small surface desquamation, and three cases had micro swelling on the face. The rash involved only the face in 5 cases, the face and trunk in 5 cases, and the face, trunk, hands, and feet in 1 case. Seven of the ten patients were pruritic, and 3 had no obvious pruritus. The histopathological features were mild epidermal hyperplasia, lymphocytic and eosinophilic infiltration around the superficial middle dermal vessels and appendages, and eosinophilic and neutrophilic abscesses in the local hair follicles. Treatment with oral indomethacin, prednisone, and minocycline was effective.Keywords: eosinophilic pustular folliculitis, eosinophils, indomethacin